Event-Related Potentials in Young and Elderly Adults during a Visual Spatial Working Memory Task - Knott, Verner; Millar, Anne; Dulude, Louise; Bradford, Lisa; Alwahhabi, Fahad; Lau, Tim; Shea, Catherine; Wiens, Andrew (Clinical EEG and neuroscience, 2004)
The P300 event-related brain potential (ERP) was examined in 14 young (20–29 years of age) and 16 elderly (60–82 years of age) subjects during the performance of a visuospatial memory task requiring recognition of locations. Elderly and young adults exhibited similar recognition accuracy, but recognition reaction times were significantly slower in the elderly. Midline P300 amplitudes recorded in response to visuospatial probe stimuli were significantly attenuated in the elderly, and, depending on the nature of the probe, P300 latency-derived indices indicated that both cognitive and motoric slowness characterized visuospatial recognition in the aged. The results, discussed in relation to neural mechanisms supporting working memory function, suggest that alterations in attention and processing speed may play a role in visual-spatial working memory deficits associated with normal and pathological aging.